2018
DOI: 10.17816/kmj2018-215
|View full text |Cite
|
Sign up to set email alerts
|

Study of effectiveness of antiviral drugs (umifenovir, triazavirin) against acute respiratory viral infections

Abstract: Aim. Comparative study of clinical efficacy and safety of antiviral drug triazavirin and umifenovir in the treatment of patients with acute respiratory viral infections and influenza. Methods. The study included 100 patients aged 18 to 65 years diagnosed with moderate acute respiratory viral infection. Group 1 included 34 patients receiving umifenovir 200 mg 4 times a day for 5 days, and comparison group included 32 patients who received triazavirin 1 capsule (250 mg) 3 times a day for 5 days. Group 3 (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…medication Triazavirin (2-methylsulfanyl-6-nitro [1,2,4]triazolo [5,1-c] [1,2,4]triazin-7-one sodium salt dihydrate) showed a broad spectrum of antiviral action and high efficacy. The medication protects against infection caused by influenza viruses, [6][7][8][9] ARVI, 10 tick-borne encephalitis. 11,12 Triazavirin has been shown to be effective in treating patients with moderate COVID-19.…”
mentioning
confidence: 99%
“…medication Triazavirin (2-methylsulfanyl-6-nitro [1,2,4]triazolo [5,1-c] [1,2,4]triazin-7-one sodium salt dihydrate) showed a broad spectrum of antiviral action and high efficacy. The medication protects against infection caused by influenza viruses, [6][7][8][9] ARVI, 10 tick-borne encephalitis. 11,12 Triazavirin has been shown to be effective in treating patients with moderate COVID-19.…”
mentioning
confidence: 99%
“…By functioning as molecular glue, Arbidol stabilizes the prefusion conformation of HA that inhibits the large conformational rearrangements associated with membrane fusion in the low pH of the endosome [239]. Arbidol has been found to reverse the main symptoms, reduce incidence of complications and contribute to the stabilisation of adaptive reactions in patients with acute respiratory viral infections [240]. A study of 100 patients with COPD or asthma found that seasonal and post-exposure prophylaxis using Arbidol (Umifenovir) was associated with 2.6-times reduction in influenza and acute respiratory viral infection related morbidity during an epidemic period.…”
Section: Sialic Acid (Sa) and Haemagglutinin A (Ha-a)mentioning
confidence: 99%
“…This substance is effective against a wide range of influenza viruses, including H1N1, H3N2, H5N1, H5N2 and H9N2 strains [ 3 , 4 , 5 , 6 , 7 ]. It is worth noting that TZV is a drug with rather low toxicity.…”
Section: Introductionmentioning
confidence: 99%